IMPLEMENTASI CLOUD STORAGE MENGGUNAKAN OWNCLOUD DAN UBUNTU SERVER STUDI KASUS PADA PT INDONESIA NIPPON SEIKI - Waliadi Gunawan; Elan Sunandar (Journal of Innovation And Future Technology (IFTECH), 2021)
The purpose of this study was to produce real work based on the need for cloud storage for ease in the company's business processes which in its benefits are intended for file sharing in the e-mail delivery process and provide security for attached files because infrastructure such as servers and storage media are within the scope of the company. The research method that I use is the prototype method, where the author first analyzes the needs and from the results of the analysis the authors design the stages that will be carried out and use UML (Unified Modeling Language) as a software modeling tool developed. The results achieved are that the file sharing facility in cloud storage can be used as a medium for sending large files in the process of sending e-mails by uploading files to be sent into cloud storage to then get the download link to be sent via e-mail to then downloaded by the recipient user, and information security can be better maintained because all infrastructure both from the server and storage media are within the scope of the company, this is done to prevent theft of information by irresponsible parties. The conclusion is that before applying cloud storage, the maximum limit for sending email is only 5 Mb, after cloud storage is implemented at the company, the business process of sending e-mails with large file attachment sizes is not a problem because users can utilize cloud storage facilities, and data security. To be guaranteed because cloud storage infrastructure is within the scope of the company.